PENCEMARAN LINGKUNGAN AKIBAT LIMBAH INDUSTRI: STUDI KASUS DI SEKITAR PT. X - Hoerul, Ade; Manfaluthi, Daffa Al; Febriyani, Metha Nur (Taksasila Edukasi Insani, 2026)
The study examined the pollutants caused by industrial waste at illegal waste disposal sites (tpa) that are run by pt. jaya real x estate in south tangattacked. By using descriptive qualitative methods through deep interviews with affected citizens, the study identifies the forms, effects and responses of people to the problem of pollution. Research indicates that people have been exposed to severe air and soil pollution since the landfall, marked by the strong stench of organic waste decay (methane, ammonia, hydrogen sulfide) and the buildup of nontreated inorganic waste such as styrofoam and foam. Health effects include respiratory problems and skin diseases among citizens. Though there have been several reports to local authorities (rt, rw, and district office), inadequate responses, showing weak environmental law enforcement. Although the landmine had been shut down a month before the study was made, pollutants still continued, showing the systemic failure of waste management and environmental monitoring. The study concluded that proper lack of permission (amdal, ukl/upl), lack of community participation, and inadequate corporate social responsibility have led to environmental injustice. It recommends increased environmental monitoring, transparent waste management systems, and ensuring public involvement in decision-making processes regarding environmental management.Keywords : environmental pollution, industrial waste, illegal landfill, public health, environmental justice